2011
DOI: 10.1124/mol.111.072249
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Estrogen Receptor Modulator Bazedoxifene Inhibits Hormone-Independent Breast Cancer Cell Growth and Down-Regulates Estrogen Receptor α and Cyclin D1

Abstract: Bazedoxifene (BZA) is a third-generation selective estrogen receptor modulator (SERM) that has been approved for the prevention and treatment of postmenopausal osteoporosis. It has antitumor activity; however, its mechanism of action remains unclear. In the present study, we characterized the effects of BZA and several other SERMs on the proliferation of hormone-dependent MCF-7 and T47D breast cancer cells and hormone-independent MCF-7:5C and MCF-7:2A cells and examined its mechanism of action in these cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 38 publications
6
89
0
2
Order By: Relevance
“…Bazedoxifene antagonizes estrogen-stimulated proliferation of MCF-7 breast cancer cells with little to no effects in uterine and CNS tissue, and also maintains bone density, reduces cholesterol in rats, and causes regression of endometriosis in mice (Komm and Lyttle, 2001;Komm et al, 2005;Ronkin et al, 2005;Kulak et al, 2011). Bazedoxifene inhibits the proliferation of estrogen-dependent (MCF-7 and T47D) and estrogenindependent (MCF-7:5C and MCF-7:2A) cell lines (Lewis-Wambi et al, 2011). Its ability to antagonize growth of MCF-7:5C cells in particular is unique among SERMs and occurs as a result of downregulation of ERa (via protein degradation) and suppressing cyclin D1 expression.…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%
“…Bazedoxifene antagonizes estrogen-stimulated proliferation of MCF-7 breast cancer cells with little to no effects in uterine and CNS tissue, and also maintains bone density, reduces cholesterol in rats, and causes regression of endometriosis in mice (Komm and Lyttle, 2001;Komm et al, 2005;Ronkin et al, 2005;Kulak et al, 2011). Bazedoxifene inhibits the proliferation of estrogen-dependent (MCF-7 and T47D) and estrogenindependent (MCF-7:5C and MCF-7:2A) cell lines (Lewis-Wambi et al, 2011). Its ability to antagonize growth of MCF-7:5C cells in particular is unique among SERMs and occurs as a result of downregulation of ERa (via protein degradation) and suppressing cyclin D1 expression.…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%
“…The SERMs, BAZ, and tamoxifen inhibit ERa activity in breast cancer cells (Lewis-Wambi et al, 2011;Cirillo et al, 2013). However, these drugs inhibit ERa activity through different mechanisms.…”
Section: Dual Inhibition Of Era By Tissue-selective Estrogen Complexmentioning
confidence: 99%
“…However, the difference is in the amino acid residues and the site of interaction. These indicated that the shapes of the hERα and cERα binding pockets are different between the two species [23,24] . Among the different key amino acid residues, E354 formed hydrogen bonding with both E2 and bazedoxifene.…”
Section: Discussionmentioning
confidence: 99%